Kontribusi Sit Up Dan Back Up Terhadap Keterampilan Throw In pada Siswa Ssb Harapan Bangsa Usia 17-21 Tahun - Andes Permadi; Oddie Barnanda Rizky; Adnan Dermawan (SPORT GYMNASTICS : Jurnal Ilmiah Pendidikan Jasmani, 2022)
ABSTRACTThis study aims to determine the contribution of Sit ups and Back ups to throwing skills in SSB Harapan Bangsa students aged 17-21 years. The method used in this research is quantitative. The sample of this research is 35 students of SSB Harapan Bangsa aged 17-21 years. The data obtained from the research carried out can be obtained that there is a contribution of Sit ups to the throwing skills of SSB Harapan Bangsa students aged 17-21 years, with the value of r_xy = 0.735. Then there is the back-up contribution to the throw-in skill for SSB Harapan Bangsa students aged 17-21 years, with a value of r_xy=0.718. This shows the contribution of Sit ups and Back ups to the throwing skills of SSB Harapan Bangsa students aged 17-21 years. The contribution of Sit ups to the throw-in skills of SSB Harapan Bangsa students aged 17-21 years is 54,02%, and the contribution of back-ups to the throw-in skills of SSB Harapan Bangsa students aged 17-21 years is 51,55%.Keywords: Back up, Contribution, Sit up, Throw In